Survival of Clostridium difficile spores at low water activity. (August 2017) - Deng, Kai; Talukdar, Prabhat K.; Sarker, Mahfuzur R.; Paredes-Sabja, Daniel; Torres, J. Antonio
Abstract: Clostridium difficile is frequently found in meat and meat products. Germination efficiency, defined as colony formation, was previously investigated at temperatures found in meat handling and processing for spores of strain M120 (animal isolate), R20291 (human isolate), and DK1 (beef isolate). In this study, germination efficiency of these spore strains was assessed in phosphate buffered saline (PBS, a w ∼1.00), commercial beef jerky ( a w ∼0.82/0.72), and a w -adjusted PBS ( a w ∼0.82/0.72). Surface hydrophobicity was followed for spores stored in PBS. After three months and for all PBS a w levels tested, M120 and DK1 spores showed a ∼1 decimal reduction in colony formation but this was not the case when kept in beef jerky suggesting a protective food matrix effect. During storage, and with no significant a w effect, an increase in colony formation was observed for R20291 spores kept in PBS (∼2 decimal log increase) and beef jerky (∼1 decimal log increase) suggesting a loss of spore superdormancy. For all strains, no significant changes in spore surface hydrophobicity were observed after storage. Collectively, these results indicate that depending on the germination properties of C . difficile spores and the media properties, their germination efficiency may increase or decrease during long term food storage. Highlights: Clostridium difficile spore germination efficiency varies with strain, aw & media. Strain R20291 germination efficiency increased when stored in reduced media. Changes in spore surface hydrophobicity and germination efficiency do not correlate.